Beyond conventional wisdom in development policy : an intellectual history of UNCTAD 1964-2004 (UN New YorkUS, 2004)
Presents a collection of case studies which describe how a particular intellectual topic in UNCTAD's analytical work has evolved. Contains on CD-ROM principal offical documents that are considered to be most relevant to the individual papers.
Bibliography: p. 287-303